2022
DOI: 10.1016/j.cegh.2021.100949
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and triggering factors of unintended pregnancies among women in India: Evidence from Indian Demographic and Health Survey 2015–2016

Abstract: The primary focus of this study was to estimate the prevalence and assess the associated risk factors that impact unintended pregnancies among women who were married in India.Study design: This study utilized a cross sectional study design. Methods: It was a cross-sectional study on 32224 pregnant women that was extracted from the most recent Demographic and Health Study organized from 2015 to 2016 (round 7) in India. Facts and statistics were examined by utilizing different data analysis techniques, i.e., uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
3
3
2
Order By: Relevance
“…Consistent with a study in Tanzania [26] where higher odds of unintended pregnancy was recoded among adolescents than older women. This outcome is similar to findings of studies in India [27] and Ugandan [28]. This might simply be as a result of ignorance or limited in-depth knowledge about contraceptives use or birth control and knowledge on reproductive system on the part of adolescents.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with a study in Tanzania [26] where higher odds of unintended pregnancy was recoded among adolescents than older women. This outcome is similar to findings of studies in India [27] and Ugandan [28]. This might simply be as a result of ignorance or limited in-depth knowledge about contraceptives use or birth control and knowledge on reproductive system on the part of adolescents.…”
Section: Discussionsupporting
confidence: 83%
“…Also, in our study women who are undecided or no more desire to have children tend to experience lower odds of unintended pregnancies than women who desire for children. Similar study in India confirmed that women who are undecided or no longer desire to have children tend to experience lower prevalence of unintended pregnancies than women who desire for children [37]. Economic and high cost of living could partly be the reason; Women who have already had two or more children may have reached their desired family size due to economic constraints [38].…”
Section: Discussionmentioning
confidence: 73%
“…The findings of this study show that multiple factors cause unintended pregnancy. Some key leading factors found were family planning, CEB, fertility preference, and wealth status, consistent with the study conducted by Islam et al (2022). Concerning the status of these factors, the Ministry of Health [Nepal] et al (2017) reported an increasing trend of age at first marriage and knowledge and use of family planning.…”
Section: Multivariate Logistic Regression Analysissupporting
confidence: 81%
“…For this study, Independent variables have been selected based on some literature works (e.g., Connery et al, 2014;Islam et al, 2022;Kotchick et al, 2001;MacAfee et al, 2019). The independent variables were categorized into different factors based on the NDHS report (Ministry of Health [Nepal] et al, 2017), such as demographic (age of respondents, age at first cohabitation, and number of household members), socioeconomic (caste and ethnicity, educational status, wealth index, media exposed and types of residence), fertility and its preference, (age at first birth, children ever born, experience of terminated pregnancy, fertility preference and desired number of children) and unmet need of family planning.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation